Planning Public Financial Management Reforms in Pacific Island Countries : Guidance Note - World Bank (Washington, DC, 2014)
This note provides guidance on planning, prioritizing, and accessing appropriate capacity for Public Financial Management (PFM) reform in Pacific Island Countries (PICs). It is intended for use by government officials, donor agencies, and consultants. It complements, and is consistent with, extensive previous work carried out by the Pacific Financial Technical Assistance Center (PFTAC) and joint efforts by the Public Expenditure and Financial Accountability (PEFA) Secretariat, International Monetary Fund (IMF), and European Commission. Recommendations are based on a review of the literature and experiences of PFM reform in the region to date, with a focus on issues that are of particular relevance in PICs. Author start point that creative approaches are sometimes needed to PFM reform in Pacific Countries because of the extent and duration of capacity constraints. Authors have two key messages. Firstly, PFM capacity should be prioritized to areas that matter most in achieving development outcomes, and reforms should be intended to address specific, identified, problems, rather than to achieve blueprint 'good practice' standards. Secondly, with small numbers of staff and high staff turnover limiting potential for sustainable gains from standard capacity building solutions, broader options for meeting capacity gaps should be considered, including accessing ongoing support for specialized tasks or even the wholesale 'outsourcing' of certain functions.